Description of a new species of Leptochilus (Neoleptochilus) Blüthgen, 1961 (Hymenoptera: Vespidae: Eumeninae) from India - P. Girish Kumar; J. M. Carpenter (Journal of Threatened Taxa, 2015)
A new species, Leptochilus (Neoleptochilus) hassani is described from India and compared with similar already described species: Leptochilus (Neoleptochilus) insitivus Gusenleitner, 1976 and L. (N.) umerolatus Gusenleitner, 2006.  A checklist of the species of Leptochilus (Neoleptochilus) from the Indian subcontinent is also provided.